THE EFFECT OF HUMAN RESOURCES (HR) QUALITY, E-COMMERCE ROLE, AND CAPITAL ACCESS ON MSME PERFORMANCE - Putri Yufi Angraeni; Nursiam Nursiam (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
This research delves into the Effect of HR Quality, E-commerce Role, and Capital Access on MSME Performance in Surakarta City. Employing a quantitative methodology, the research surveyed 97 MSME respondents selected through the Lemeshow formula, utilizing both accidental and simple random sampling techniques. Data were gathered through online questionnaires via Google Form and analyzed using SPSS version 25 through multiple linear regression. The results reveal that while the quality of human resources and the role of e-commerce do not significantly influence MSME performance, access to capital has a positive and substantial effect. These findings highlight the necessity for a stronger emphasis on financial accessibility to enhance MSME performance in Surakarta, such as offering affordable loans or flexible funding options. Although improving human resource quality and leveraging e-commerce remain vital, they must be underpinned by appropriate structural and financial mechanisms. Policymakers are encouraged to prioritize financial support systems, while MSMEs should enhance their digital marketing strategies and ensure robust technological infrastructures to facilitate effective e-commerce integration.